2021
DOI: 10.1128/jb.00073-21
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Vortices with Dynamic Rotation Emerged from Monolayer Collective Motion of Gliding Flavobacteria

Abstract: A collective motion of self-driven particles has been a fascinating subject in physics and biology. Sophisticated macroscopic behavior emerges through a population in thousands or millions of bacterial cells, propelling itself by flagellar rotation and its chemotactic response. Here we found a series of collective motions accompanying successive phase-transitions in a non-flagellated rod-shaped soil bacterium, Flavobacterium johnsoniae , which was driven by a surface cell movement known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…It has long been known that F. johnsoniae forms spreading colonies on agar plates ( Wolkin and Pate, 1984 ; Gorski et al, 1993 ). A recent study showed that the cells at high density are connected with one another and that in a starved environment they move in counterclockwise trajectories ( Nakane et al, 2021 ). A F. johnsoniae swarm exhibits a vortex pattern that spontaneously appears as a lattice that is integrated into a large-scale circular plate ( Figure 3A ).…”
Section: Accessory Proteins Not Required For Gliding Motilitymentioning
confidence: 99%
See 1 more Smart Citation
“…It has long been known that F. johnsoniae forms spreading colonies on agar plates ( Wolkin and Pate, 1984 ; Gorski et al, 1993 ). A recent study showed that the cells at high density are connected with one another and that in a starved environment they move in counterclockwise trajectories ( Nakane et al, 2021 ). A F. johnsoniae swarm exhibits a vortex pattern that spontaneously appears as a lattice that is integrated into a large-scale circular plate ( Figure 3A ).…”
Section: Accessory Proteins Not Required For Gliding Motilitymentioning
confidence: 99%
“…This two-dimensional pattern possibly appears due to the collision of cells and it further induces a nematic alignment of dense cells ( Sumino et al, 2012 ). It is hypothesized that swarm behavior of T9SS driven Bacteroidetes may be involved in survival strategies and the efficient search of nutrients ( Figure 3C ; Nakane et al, 2021 ). A three-dimensional spherical microcolony was recently studied in a microfluidic device and it was reported that this biofilm-like microcolony self-assembles by the gliding motility ( Li et al, 2021 ).…”
Section: Accessory Proteins Not Required For Gliding Motilitymentioning
confidence: 99%
“…It is made available under a preprint (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in The copyright holder for this this version posted January 11, 2022. ; https://doi.org/10.1101/2022.01.10.475764 doi: bioRxiv preprint direction (Student's t-test, p << 0.01). Interestingly, Flavobacterium johnsoniae was also recently shown to perform gliding motility and vortex formation with the CCW preference (6). It shows a CCW trajectory even from the singlecell state, and remains unified in the CCW direction while rotating as a group, but moves in the CW direction just before it stops its rotation.…”
Section: Counterclockwise Movement Is More Stable For High Density Clustersmentioning
confidence: 99%
“…Although the distribution of probability density for median perturbation angle and duration showed no significant difference in the distribution of median perturbation angle between CCW and CW (Mardia-Watson-Wheeler test, p = 0.6369), the duration of the CCW direction was statistically longer than that of the CW direction (Student's t-test, p << 0.01). Interestingly, Flavobacterium johnsoniae was also recently shown to perform gliding motility and vortex formation with the CCW preference (6). It shows a CCW trajectory even from the singlecell state, and remains unified in the CCW direction while rotating as a group, but moves in the CW direction just before it stops its rotation.…”
Section: Counterclockwise Movement Is More Stable For High Density Clustersmentioning
confidence: 99%
“…Using a variety of different molecular appendages, they move by sliding, gliding, twitching and swimming (10). However, it is surface-associated motility mechanisms such as gliding motility or Type IV pilus-based twitching motility that are most commonly used when cells are at the high cell densities where contact-based weapons are effective (11, 12). Consistent with this, these conditions are also closely associated with the expression of T6SS (13) and CDI genes (14).…”
Section: Introductionmentioning
confidence: 99%